The impact of indoor air quality on respiratory health of older people: spirometric and exhaled breath condensate assessments - Belo, Joana (2019)
In general, seven million deads are dur to the indoor and outdoor environment exposure. The elderly are identified as the one of the principal risk groups: the progressive decline of biological functions; cumulative environmental exposure; 90% of the time is in indoor spaces. The main goal of this study was to describe the impact of environmental exposure from the point of view of IAQ in respiratory health in a sample of elderly people living in nursing homes. The elderly were evaluated through spirometry and exhaled breath condensate (EBC).